The influence of internet-based financial innovations on the supply chain performance of halal SMEs - Jaiyeoba, Haruna Babatunde; Mohd Salleh, Hamzah; Che Embi, Nor Azizan; Bahari, Siti Suryati (Springer Nature, 2025)
In an era characterised by technological advancements, the adoption of Internet-based financial innovations has become imperative for the growth and sustainability of halal SMEs. Despite the importance of Internet-based financial innovation in enhancing supply chain performance, there is a dearth of evidence regarding how these innovations have contributed to the supply chain performance of halal SMEs. Thus, this research examines the influence of Internet-based financial innovations on supply chain performance of halal SMEs in Malaysia. Utilising a quantitative research design, a comprehensive survey questionnaire was developed based on the existing literature. Data were collected from 158 halal SME owners and managers in Malaysia, employing both face-to-face and online data collection methods. Subsequent data analysis incorporated exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modelling (SEM). The results indicate that e-payment and e-commerce positively and significantly contribute to the supply chain performance of halal SMEs. However, the influence of online loan services on supply chain performance, while positive, was found to be statistically insignificant. Meanwhile, managerial innovativeness was found to fully mediate the relationship between e-payment and supply chain performance, as well as the relationship between online loan services and supply chain performance, but only partially mediates the relationship between e-commerce and supply chain performance. Therefore, this research makes a significant contribution to the body of knowledge by introducing financial innovation integration through e-payments, e-commerce, and online lending as a key component of supply chain coordination, particularly in Halal contexts where traceability and trust are essential